Secondary treatment method for metal magnetic powder core coated granulation defective powder
Patent Information
- Application Number
- CN202611367758.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]然而,上述方案均属于预防性措施,旨在通过前端工艺优化降低缺陷发生率,一旦粉料已形成软趴缺陷,则缺乏有效的补救手段
本公开通过对已出现软趴缺陷的包覆造粒粉料进行二次溶解、微量补胶和再造粒处理,使缺陷粉料恢复为颗粒感明显、流动性良好的可用状态,可直接用于后续压制成型工序,避免了整批粉料报废造成的原材料和工时浪费。由于补充粘结剂加入量仅为缺陷粉料质量的0.1%~1.0%,远低于初始包覆时的粘结剂用量,不会导致绝缘层增厚而影响磁性能,处理后的再生粉料在磁导率和损耗方面与正常粉料基本相当。该方法仅涉及溶解、补胶、造粒和烘干等常规操作,无需对磁粉进行重新绝缘包覆,利用现有生产设备即可实施,工艺简单、成本低廉,适合工业化推广。
Smart Images

Figure CN122889574A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of soft magnetic metal materials technology, and more specifically, to a secondary treatment method for defective powder materials coated with metal magnetic powder cores. Background Technology
[0002] Metal magnetic powder cores are composite soft magnetic materials formed by pressing soft magnetic powder into shape after passivation and insulating coating. They have both high saturation magnetic induction intensity and low high-frequency loss characteristics, and are widely used in inductors and transformers in power electronic equipment such as switching power supplies, photovoltaic inverters, new energy vehicle charging piles and frequency converters.
[0003] In the industrial production of metal magnetic powder cores, the process from alloy powder to the final magnetic core product typically involves the following steps: alloy smelting → atomization powder preparation → powder passivation → insulation coating → adhesive mixing → granulation → pressing and molding → annealing. Among these, the adhesive mixing and granulation processes have a decisive impact on the density uniformity, magnetic property consistency, and yield of the final magnetic core. In this process, operators dissolve insulating binders (such as epoxy resin, silicone resin, etc.) in an organic solvent and stir them with the passivated magnetic powder in a mixing device. This ensures the binder is evenly dispersed on the surface of the powder particles. The powder is then dried to remove the solvent and granulated and sieved to obtain a coated powder with a specific particle size distribution and flowability, ready for subsequent pressing and molding.
[0004] In production practice, even with strict control over raw material ratios, stirring speeds, and drying parameters, batch-to-batch fluctuations in the state of the coated and granulated powder still occur. Specifically, some batches of powder exhibit indistinct granular texture, a soft feel, and significantly reduced flowability after drying and granulation—a state commonly referred to in the industry as "soft and limp." Testing reveals that the angle of repose of this type of powder is typically above 45°, far exceeding the normal 30°~35°. Powder in this state cannot evenly fill the mold during pressing, easily leading to defects such as large deviations in green density, core cracking, or missing corners. In severe cases, the entire batch of powder must be scrapped, resulting in significant waste of raw materials and labor.
[0005] To address the aforementioned issues, existing technologies primarily focus on improvements in two directions: First, optimizing granulation process parameters. For example, CN113744988A proposes precisely controlling the moisture content of the granulated powder within the range of 0.6% to 0.7% and drying it in a vacuum environment to improve powder appearance and reduce cracking; CN118658692A proposes performing at least two coating treatments on the alloy powder, combined with independent annealing, to reduce core loss. Second, improving the coating material. For instance, some studies have introduced coupling agents during the coating process to anchor the resin to the magnetic powder surface, thereby improving the uniformity and bonding strength of the coating layer.
[0006] However, the above-mentioned solutions are all preventative measures, aiming to reduce the defect rate through front-end process optimization. Once the powder has developed a soft-pack defect, there is a lack of effective remedial measures. In actual production, defective powder is usually directly scrapped or downgraded, resulting in high material loss costs. Therefore, there is an urgent need for a method to remediate coated granulated powder that has developed a soft-pack defect, restoring the defective powder to a usable state, thereby reducing the scrap rate and saving production costs.
[0007] In view of this, this disclosure is hereby made. Summary of the Invention
[0008] The purpose of this disclosure is to provide a secondary treatment method for defective powder materials coated with metal magnetic powder cores.
[0009] This disclosure is implemented as follows: In a first aspect, this disclosure provides a secondary treatment method for defective powder materials coated with metal magnetic powder cores, comprising the following steps: (1) Take the defective metal magnetic powder core material that has been coated with binder, dried and granulated and is in a soft state; The term "soft and limp state" refers to a state where the graininess is not obvious and the fluidity is poor. (2) Add organic solvent to the defective powder described in step (1), stir evenly, so that the solidified binder in the powder can be redissolved and the powder can be restored to a wet state; The moist state refers to a paste-like or plastic state; (3) Add supplementary binder to the wet material obtained in step (2), stir evenly, so that the supplementary binder is mixed with the original binder; The amount of the supplementary binder added is 0.1% to 1.0% of the mass of the defective powder; (4) The material obtained in step (3) is granulated and dried to obtain recycled powder.
[0010] In an optional implementation, in step (1), the angle of repose of the defective powder is 45° or more.
[0011] In an optional embodiment, in step (2), the amount of organic solvent added is 5% to 30% of the mass of the defective powder.
[0012] In an optional embodiment, in step (2), the organic solvent is selected from one or more of acetone, ethanol, toluene, and xylene.
[0013] In an optional implementation, in step (3), the supplementary binder is the same type of binder used in the initial coating granulation in step (1).
[0014] In an optional embodiment, in step (3), the supplementary adhesive is selected from one or more of epoxy resin, silicone resin, and phenolic resin.
[0015] In an optional embodiment, in step (3), the amount of the supplementary binder added is 0.2% to 0.6% of the mass of the defective powder.
[0016] In an optional embodiment, in step (4), the granulation is carried out by screen granulation or high-speed stirring granulation, and the granulation mesh is 20 mesh to 120 mesh.
[0017] In an optional implementation, in step (4), the drying temperature is 60℃~150℃ and the drying time is 1~6 hours.
[0018] In an optional implementation, in step (4), the moisture content of the resulting recycled powder is 0.6% to 0.7%.
[0019] This disclosure has the following beneficial effects: This disclosure describes a process involving secondary dissolution, micro-adhesive addition, and regranulation of coated granulated powder exhibiting softness defects. This restores the defective powder to a usable state with a distinct granular texture and good flowability, allowing it to be directly used in subsequent pressing and molding processes. This avoids the waste of raw materials and labor caused by scrapping the entire batch of powder. Since the amount of supplementary binder added is only 0.1% to 1.0% of the defective powder's mass, far lower than the amount used during initial coating, it does not cause the insulation layer to thicken and affect magnetic properties. The treated regenerated powder is essentially equivalent to normal powder in terms of magnetic permeability and loss. This method involves only conventional operations such as dissolution, adhesive addition, granulation, and drying, without requiring re-insulation coating of the magnetic powder. It can be implemented using existing production equipment, is simple in process, low in cost, and suitable for industrial-scale promotion. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this disclosure and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 Scanning electron microscope (SEM) image of the powder material with pre-softening defects.
[0022] Figure 2 This is a scanning electron microscope (SEM) image of the recycled powder obtained after secondary processing.
[0023] Figure 3 This is a comparison of actual magnetic cores made from defective powder and magnetic cores made from recycled powder.
[0024] Figure 4 A comparison of the surface quality of magnetic cores pressed directly from defective powder and those pressed from recycled powder. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions in the embodiments of this disclosure will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] In a first aspect, this disclosure provides a secondary treatment method for defective powder materials coated with metal magnetic powder cores, comprising the following steps: (1) Take the defective metal magnetic powder core material that has been coated with binder, dried and granulated and is in a soft state; The term "soft and limp state" refers to a state where the graininess is not obvious and the fluidity is poor. (2) Add organic solvent to the defective powder described in step (1), stir evenly, so that the solidified binder in the powder can be redissolved and the powder can be restored to a wet state; The moist state refers to a paste-like or plastic state; (3) Add supplementary binder to the wet material obtained in step (2), stir evenly, so that the supplementary binder is mixed with the original binder; The amount of the supplementary binder added is 0.1% to 1.0% of the mass of the defective powder; (4) The material obtained in step (3) is granulated and dried to obtain recycled powder.
[0027] The purpose of this disclosed method is to remedy defects in powder materials that have undergone binder coating and drying granulation through secondary processing. Step (1) limits the processing object to defective powder materials in a soft, limp state, which refers to a state where the particle texture is not obvious and the flowability is poor. Powder materials in this state cannot be directly used in subsequent pressing and molding processes because the poor flowability of the powder materials leads to uneven filling of the mold, which in turn causes defects such as uneven density distribution of the green body and magnetic core cracks. Step (2) involves adding an organic solvent to redissolve the solidified binder in the powder materials. The principle is that the organic solvent can penetrate and soften the dense adhesive film, causing the solidified binder to redissolve and restore its adhesiveness. The powder materials are restored to a moist state in a paste or plastic state, at which point the material has the plasticity to be re-granulated. The purpose of adding a small amount of binder in step (3) is to repair the micro-cracks that may have occurred in the original adhesive layer during the first drying process, and to re-bond the broken small particles into a solid particle skeleton. The amount added is controlled at 0.1% to 1.0% of the defective powder mass, which is much lower than the amount of binder added during the initial coating (usually 2% to 3%). This ensures the recovery of particle strength while avoiding excessive binder that could lead to a decrease in magnetic permeability or an increase in loss. This step is the key to restoring particle strength. Step (4) Through secondary granulation and drying, the material is reformed into a recycled powder with good particle texture and flowability, which can be directly used in the subsequent pressing and molding process.
[0028] Furthermore, the so-called soft state refers to the defective powder being viscous and lacking flowability (flow rate test result: 0s).
[0029] In an optional implementation, in step (1), the angle of repose of the defective powder is 45° or more.
[0030] The angle of repose is a recognized measurable parameter in powder engineering, used to objectively characterize the flowability of powders. A larger angle of repose indicates poorer powder flowability. The angle of repose of normal metal magnetic core-coated granulated powders is typically in the range of 30° to 35°. When the angle of repose reaches 45° or higher, it indicates that the powder is in a soft, mushy state with indistinct granular texture and poor flowability, failing to meet the flowability requirements of the compression molding process.
[0031] In an optional embodiment, in step (2), the amount of organic solvent added is 5% to 30% of the mass of the defective powder.
[0032] The amount of organic solvent added is a key parameter affecting the dissolution effect of the binder and the subsequent drying efficiency. When the amount of solvent added is less than 5%, the amount of solvent is insufficient to fully dissolve the cured binder, and the powder cannot be completely restored to a paste or plastic state, affecting the subsequent glue addition and granulation effect. When the amount of solvent added is more than 30%, although the dissolution effect is good, the solvent evaporation requires a longer drying time and higher energy consumption, and excessive solvent may cause the powder to be too wet and difficult to granulate.
[0033] In an optional embodiment, in step (2), the organic solvent is selected from one or more of acetone, ethanol, toluene, and xylene.
[0034] The aforementioned organic solvents all exhibit good solubility for common magnetic powder core coating binders (epoxy resin, silicone resin, phenolic resin, etc.). Acetone shows excellent solubility in epoxy resin with a moderate evaporation rate, ethanol has a good solubility in silicone resin, while toluene and xylene are suitable for binders with lower solubility, such as phenolic resin. In practical applications, a matching solvent can be selected based on the type of binder used for initial coating, or two or more solvents can be mixed in a certain proportion to balance solubility and evaporation rate.
[0035] In a preferred embodiment, the organic solvent is a mixture of acetone and ethanol, with a volume ratio of 1:0.5 to 1:2.
[0036] When using a mixed solvent, the volume ratio of acetone to ethanol affects the balance between solubility and evaporation rate. Acetone has a faster evaporation rate and good solubility for epoxy resins; ethanol has a slower evaporation rate and good solubility for silicone resins. A volume ratio between 1:0.5 and 1:2 can balance the solubility for different types of binders while controlling the solvent's evaporation rate to match the subsequent drying process. In Example 3, a 1:1 volume ratio of acetone to ethanol was used to treat phenolic resin-coated powder, achieving good dissolution and granulation effects.
[0037] In an optional implementation, in step (3), the supplementary binder is the same type of binder used in the initial coating granulation in step (1).
[0038] Using the same type of adhesive as the initial coating ensures that the supplementary adhesive is consistent with the original adhesive in terms of chemical properties, curing conditions, and coefficient of thermal expansion. This avoids problems such as internal stress within the particles, poor interfacial bonding, or delamination during subsequent heat treatment caused by adhesive type mismatch. For example, if epoxy resin is used for the initial coating, epoxy resin should also be used as the supplementary adhesive; similarly, if silicone resin is used for the initial coating, silicone resin should also be used as the supplementary adhesive.
[0039] In an optional embodiment, in step (3), the supplementary adhesive is selected from one or more of epoxy resin, silicone resin, and phenolic resin.
[0040] In an optional embodiment, in step (3), the amount of the supplementary binder added is 0.2% to 0.6% of the mass of the defective powder.
[0041] In an optional implementation, in steps (2) and (3), the stirring speed is 100-500 rpm and the stirring time is 5-30 minutes.
[0042] In an optional embodiment, the metal magnetic powder core is selected from one of iron-nickel magnetic powder cores, iron-silicon-aluminum magnetic powder cores, and iron-based amorphous magnetic powder cores.
[0043] Iron-nickel magnetic powder cores possess high permeability and low loss characteristics, making them widely used in high-frequency inductor devices; iron-silicon-aluminum magnetic powder cores exhibit excellent DC bias characteristics and temperature stability; iron-based amorphous magnetic powder cores possess high saturation magnetic induction and low high-frequency loss. These three types of magnetic powder cores are the main varieties of metallic magnetic powder cores. Although their coating and granulation processes have different characteristics, all may result in powder with granulation defects. The method disclosed in this paper is applicable to all three types of magnetic powder cores.
[0044] In an optional embodiment, in step (4), the granulation is carried out by screen granulation or high-speed stirring granulation, and the granulation mesh is 20 mesh to 120 mesh.
[0045] Screen granulation is simple to operate and produces good particle uniformity, making it suitable for granulation processes of most metal magnetic powder cores. High-speed stirring granulation is highly efficient and suitable for large-scale processing. The mesh size affects the particle size and flowability of the recycled powder: too large a mesh size (too small particles) may lead to decreased powder flowability, while too small a mesh size (too large particles) may result in uneven filling during pressing. The 20-120 mesh range covers the commonly used particle size range for metal magnetic powder core pressing.
[0046] In an optional implementation, in step (4), the drying temperature is 60℃~150℃ and the drying time is 1~6 hours.
[0047] Drying temperature and time affect the solvent evaporation rate and the final moisture content of the recycled powder. If the temperature is too low (below 60°C) or the time is too short (below 1 hour), the solvent will not evaporate sufficiently, and the moisture content may exceed 0.7%, affecting subsequent pressing. If the temperature is too high (above 150°C), the binder may cure prematurely or oxidize and decompose, affecting the powder performance.
[0048] In an optional implementation, in step (4), the moisture content of the resulting recycled powder is 0.6% to 0.7%.
[0049] Moisture content is a key parameter affecting the pressing performance and magnetic properties of metal magnetic powder cores. Existing research shows that when the moisture content is higher than 0.7%, the moisture affects the granulation and pressing process, reducing the magnetic permeability of the powder core and increasing losses; when the moisture content is lower than 0.6%, the powder becomes too dry, which may lead to damage to the coating layer and poor particle morphology. Controlling the moisture content of recycled powder within the range of 0.6% to 0.7% can ensure that the recycled powder has good pressing performance and magnetic properties, consistent with the requirements of normal powder.
[0050] In a preferred embodiment, the angle of repose of the recycled powder obtained in step (4) is less than 35°.
[0051] The angle of repose of recycled powder is a direct indicator of the effectiveness of secondary treatment. Data from the examples show that after treatment using the method of this disclosure, the angle of repose of the recycled powder is 31°~35°, close to that of normal powder (approximately 30°), indicating that the powder has regained good particle texture and flowability and can be directly used in subsequent pressing and molding processes. In contrast, in the comparative example without additional binder, the angle of repose is only 45°, indicating insufficient particle strength.
[0052] In an optional embodiment, the recycled powder is mixed with normal powder at a mass ratio of 1:1 to 1:3 and then used for compression molding.
[0053] In actual production, recycled powder can be used alone or mixed with normal powder in a certain proportion. When mixed, the mass ratio of recycled powder to normal powder can be controlled within the range of 1:1 to 1:3. This ratio range makes full use of the recycled powder while ensuring product quality.
[0054] The features and performance of this disclosure will be further described in detail below with reference to embodiments.
[0055] The epoxy resin used in this embodiment is a bisphenol A type epoxy resin, commercial brand name E-44 (i.e., type 6101, epoxy value 0.41~0.47 eq / 100g); the silicone resin is a methyl silicone resin, commercial brand name SILRES® 604 (solid content approximately 50%); the phenolic resin is a thermosetting phenolic resin, commercial brand name 2123 (free phenol content ≤6%); the acetone and anhydrous ethanol used are both analytical grade, with a purity ≥99.5%.
[0056] Example 1 This embodiment involves a secondary treatment of the iron-nickel metal magnetic powder core coated granulated powder.
[0057] 1. Obtaining defective powder Iron-nickel alloy powder (Fe-50%Ni, average particle size D50=25 μm) was coated with insulating material using conventional processes. Then, 2.5% epoxy resin (dissolved in acetone) was added by weight of the magnetic powder for wet mixing. After thorough stirring, the mixture was dried and granulated. The resulting powder exhibited indistinct granular texture, a soft and yielding feel, and poor flowability, and was deemed defective. Testing revealed that the angle of repose of this defective powder was 52°, indicating a soft and yielding state with indistinct granular texture and poor flowability, making it unsuitable for direct pressing.
[0058] 2. Secondary processing Take 1000g of the above-mentioned defective powder (angle of repose 52°, in a soft, collapsed state), its scanning electron microscope morphology is as follows. Figure 1 As shown in the figure, it is placed in a granulator.
[0059] Add 150g of acetone (15% of the defective powder mass) to the granulator, turn on the stirrer, turn the speed to 200rpm, and stir for 15 minutes to redissolve the solidified epoxy resin in the powder and restore the powder to a moist paste-like material, that is, a moist state in paste or plastic form.
[0060] Add 4 g of epoxy resin (0.4% of the defective powder mass) to the above-mentioned moist material, and continue stirring for 10 minutes to ensure that the added epoxy resin is fully mixed with the original resin and evenly distributed on the surface of the magnetic powder particles. The amount of adhesive added here (0.4%) is much lower than the amount of adhesive added during the initial coating (2.5%), which is considered a micro-adhesive addition.
[0061] The above materials are granulated through a 40-mesh sieve, and then the granulated powder is placed in an oven and dried at 100°C for 3 hours to obtain recycled powder.
[0062] 3. Effectiveness Evaluation After drying, the powder is removed and cooled to room temperature. Its particle morphology is observed and a flowability test is performed.
[0063] The results showed that after the second treatment, the powder had a noticeable granular texture, was dry, and had good flowability. The angle of repose decreased from 52° before treatment to 32°, which is close to the angle of repose of normal powder (30°). The scanning electron microscope morphology was as follows. Figure 2 As shown, it can be directly used in subsequent pressing and molding processes.
[0064] The powder after secondary processing was pressed into shape and its magnetic properties were tested. The results are shown in Table 1.
[0065] Table 1 Comparison of magnetic properties before and after secondary treatment
[0066] The results show that the powder after secondary treatment is basically equivalent to the normal powder in terms of magnetic permeability and loss. The moisture content is controlled within the range of 0.6% to 0.7%. The pressed magnetic core has a complete and smooth surface, without powder shedding or edge chipping defects, and the edges are regular (e.g., Figure 3 , 4 The magnetic core has a flat surface (as shown), which meets the usage requirements.
[0067] Example 2: Secondary treatment of defective powder material from iron-silicon-aluminum magnetic powder core coating granulation The difference between this embodiment and Embodiment 1 is that the defective powder is an iron-silicon-aluminum magnetic powder core coated granulated powder, the binder used is silicone resin, the organic solvent is ethanol, and the supplementary binder is the same type of silicone resin.
[0068] The specific parameters are as follows: Take iron-silicon-aluminum alloy powder (FeSiAl, average particle size D50=30 μm), after insulating coating according to conventional process, add 2.0% of the magnetic powder mass of organosilicon resin (dissolved in ethanol) for wet mixing, stir evenly and then dry and granulate to obtain defect powder in a soft state with an angle of repose of 50°.
[0069] Take 1000 g of the above-mentioned defective powder, add 120 g of ethanol (accounting for 12% of the defective powder mass), stir and dissolve for 15 minutes to redissolve the solidified organosilicon resin in the powder, and restore the powder to a paste-like moist state; add 3 g of organosilicon resin (accounting for 0.3% of the defective powder mass), continue stirring for 10 minutes, granulate through a 60-mesh sieve, and dry at 120℃ for 2.5 hours to obtain the regenerated powder.
[0070] The results showed that after secondary treatment, the powder had a noticeably more granular texture, was drier, and had better flowability. The angle of repose decreased from 50° before treatment to 33°. The recycled powder was pressed into shape and its magnetic properties were tested. The effective magnetic permeability was 59.5 (normal powder is 60.2, a deviation of 1.2%), and the core loss was 272 mW / cm. 3 (Normal powder is 265 mW / cm) 3 The deviation is 2.6%, and the moisture content is 0.66%, which meets the usage requirements.
[0071] Example 3: Secondary treatment of defective powder material coated with iron-based amorphous magnetic powder core The difference between this embodiment and Embodiment 1 is that the defective powder is an iron-based amorphous magnetic powder core coated granulated powder, the binder used is phenolic resin, and the organic solvent is a mixture of acetone and ethanol (volume ratio 1:1).
[0072] The specific parameters are as follows: take iron-based amorphous alloy powder (average particle size D50=20 μm), perform insulation coating according to conventional process, add 2.2% of phenolic resin by mass of magnetic powder for wet mixing, stir evenly and then dry and granulate to obtain defect powder in a soft state with an angle of repose of 54°.
[0073] Take 1000 g of the above-mentioned defective powder, add 200 g of a mixed solvent of acetone and ethanol (accounting for 20% of the defective powder mass, acetone:ethanol = 1:1), stir and dissolve for 20 minutes to redissolve the solidified phenolic resin in the powder, and restore the powder to a paste-like moist state; add 5 g of phenolic resin (accounting for 0.5% of the defective powder mass), continue stirring for 10 minutes, granulate through an 80-mesh sieve, and dry at 80℃ for 4 hours to obtain regenerated powder.
[0074] The results showed that after secondary treatment, the powder had a noticeably more granular texture, was drier, and had better flowability. The angle of repose decreased from 54° before treatment to 34°. The recycled powder was pressed into shape and its magnetic properties were tested. The effective magnetic permeability was 64.2 (normal powder is 65.0, a deviation of 1.2%), and the core loss was 303 mW / cm. 3 (Normal powder is 295 mW / cm) 3 The deviation is 2.7%, and the moisture content is 0.67%, which meets the usage requirements.
[0075] Example 4 The difference between this embodiment and Embodiment 1 is that the amount of organic solvent added is 8% (80 g) of the defective powder mass, the amount of supplementary binder added is 0.2% (2 g) of the defective powder mass, the granulation mesh is 60 mesh, the drying temperature is 130℃, and the drying time is 2 hours.
[0076] The specific operation is as follows: Take 1000 g of defective iron-nickel magnetic powder core material (angle of repose 52°) from the same batch as in the example, add 80 g of acetone, stir for 20 minutes to fully dissolve the binder and restore the powder to a wet state; add 2 g of epoxy resin and continue stirring for 10 minutes; granulate through a 60-mesh sieve; dry at 130°C for 2 hours to obtain recycled powder.
[0077] The results show that under the above parameters, the secondary treatment is effective, the powder has a noticeable granular texture, and the angle of repose is 35°. The recycled powder was pressed into shape and its magnetic properties were tested. The effective permeability was 61.8 (normal powder is 63.1, a deviation of 2.1%), and the core loss was 290 mW / cm. 3 (Normal powder is 278 mW / cm) 3 The deviation was 4.3%, and the moisture content was 0.66%. This example illustrates that even with a low solvent content, good processing results can still be achieved by appropriately increasing the drying temperature and shortening the drying time.
[0078] Example 5 The difference between this embodiment and Embodiment 1 is that the amount of organic solvent added is 30% (300g) of the defective powder mass, the amount of supplementary binder added is 1.0% (10g) of the defective powder mass, the granulation mesh is 20 mesh, the drying temperature is 70℃, and the drying time is 6 hours.
[0079] The specific operation is as follows: Take 1000g of defective iron-nickel magnetic powder core material (angle of repose 52°) from the same batch as in the example, add 300g of acetone, stir for 10 minutes to fully dissolve the binder and restore the powder to a wet state; add 10g of epoxy resin and continue stirring for 10 minutes; granulate through a 20-mesh sieve; dry at 70°C for 6 hours to obtain recycled powder.
[0080] The results show that within the above parameter range, the secondary treatment is effective, the powder has a noticeable granular texture, and the angle of repose is 31°. The recycled powder was pressed into shape and its magnetic properties were tested. The effective permeability was 62.0 (normal powder is 63.1, a deviation of 1.7%), and the core loss was 283 mW / cm. 3 (Normal powder is 278 mW / cm) 3 The deviation is 1.8%, and the moisture content is 0.65%. However, if the amount of solvent used is too large, the drying time needs to be extended accordingly to ensure that the solvent evaporates completely and the moisture content meets the standard.
[0081] Comparative Example 1 Take 1000g of defective iron-nickel magnetic powder core material (angle of repose 52°) from the same batch as in the example, and add only 150g of acetone for secondary dissolution and regranulation, without adding new binder. The specific operation is as follows: add 150g of acetone, stir for 15 minutes to dissolve the binder, restore the powder to a moist state, granulate through a 40-mesh sieve, and dry at 100°C for 3 hours to obtain the powder.
[0082] The results showed that although the powder was improved to some extent after secondary dissolution and granulation with solvent, the particle strength was insufficient and it was easy to break during subsequent sieving and conveying, resulting in the reappearance of some powdery material. The improvement in flowability was limited (angle of repose 45°).
[0083] This comparative example demonstrates that adding a small amount of new binder is necessary to restore particle strength. A trace amount of additional binder can close micro-cracks on the surface of the original adhesive layer and firmly bond broken particles together, forming a more robust particle skeleton, thus ensuring the particle strength and flowability of the powder after secondary processing. In the comparative example, the angle of repose was only 45° without additional binder, while adding 0.1%~1.0% binder reduced the angle of repose to 31°~35°, showing a significant effect.
[0084] Comparative Example 2 Take 1000g of defective iron-nickel magnetic powder core material (angle of repose 52°) from the same batch as in the example, add 150g (15%) of acetone and stir for 15 minutes to dissolve the binder and restore the powder to a wet state; add 20g of epoxy resin (accounting for 2.0% of the defective powder mass, exceeding the 1.0% upper limit specified in this disclosure), continue stirring for 10 minutes, granulate through a 40-mesh sieve, and dry at 100°C for 3 hours to obtain the powder.
[0085] The results showed that when the amount of adhesive added was 2.0%, the powder had a noticeable granular texture, an angle of repose of 30°, and good flowability. However, after pressing, the effective permeability of the magnetic core was only 58.1 (63.1 for normal powder, a decrease of 7.9%), and the core loss was as high as 312 mW / cm³ (278 mW / cm³ for normal powder, an increase of 12.2%), resulting in a significant decrease in magnetic properties.
[0086] This comparative example illustrates that when the amount of adhesive added exceeds 1.0%, although the flowability is well improved, the excessive amount of adhesive leads to a thicker insulation layer, a decrease in the magnetic permeability of the magnetic powder core, and an increase in losses, which fails to meet the usage requirements.
[0087] Comparative Example 3 Take 1000 g of defective iron-nickel magnetic powder core material (angle of repose 52°) from the same batch as in Example 1, add 30 g of acetone (3% of the defective powder mass, lower than the 5% lower limit specified in this disclosure), and stir for 15 minutes. The cured epoxy resin in the powder cannot be fully dissolved, and the powder is still in an uneven state of partial dryness and partial lumps, and cannot be completely restored to a moist state of paste or plasticity. Add 4 g of epoxy resin (0.4%), continue stirring for 10 minutes, granulate through a 40-mesh sieve, and dry at 100°C for 3 hours to obtain the powder.
[0088] The results showed that when the solvent content was 3%, the powder was not uniformly processed due to insufficient dissolution of the binder. Some materials remained in a soft state, resulting in inconsistent particle strength after granulation and a large amount of broken powder during sieving. The angle of repose of the processed powder was 42°, which, although lower than the defect threshold of 45°, was still significantly higher than the 30°~35° of normal powder. The flowability had not recovered to the level of normal powder, making it unsuitable for direct compression molding.
[0089] This indicates that when the amount of organic solvent added is less than 5%, the amount of solvent is insufficient to fully dissolve the cured adhesive, and the powder cannot be completely restored to a wet state, affecting the subsequent glue addition and granulation effects.
[0090] Comparative Example 4 1000 g of the soft, flaky defect powder from the same batch as in Example 1 was taken and directly pressed without any secondary processing. During the pressing process, the powder had poor flowability and uneven filling. After demolding, a large area of powder loss and pitting appeared on the outer surface of the magnetic core, with chipped edges and missing corners. The density distribution of the green blank was uneven, making it impossible to obtain a qualified magnetic core with a complete surface (e.g., Figure 3 , Figure 4 (As shown in the image: a magnetic core with a rough surface and missing edges).
[0091] The results show that the defective powder in a soft state cannot be used directly in the pressing and molding process. Without secondary treatment, it will cause defects such as powder shedding, pitting, and edge chipping on the magnetic core surface, and the entire batch of powder will have to be scrapped, which confirms the necessity of secondary treatment of defective powder.
[0092] Table 2. Effects of different glue application amounts on treatment effect and magnetic properties
[0093] Table 2 shows that when the amount of adhesive added is within the range of 0.1% to 1.0%, the powder has good flowability (angle of repose below 35°) and its magnetic properties are basically equivalent to those of normal powder (effective permeability deviation less than 3%, loss deviation less than 5%). In Comparative Example 1, when the amount of adhesive added is 0, the particle strength is insufficient. In Comparative Example 2, when the amount of adhesive added exceeds 1.0% and reaches 2.0%, although the flowability is further improved, the permeability decreases by 7.9%, the loss increases by 12.2%, and the magnetic properties deteriorate significantly. Therefore, limiting the amount of adhesive added to 0.1% to 1.0% of the defective powder mass is reasonable.
[0094] Example 6 To verify the industrial applicability of the method disclosed herein, a pilot-scale test was conducted on a production line.
[0095] Take 50 kg of iron-nickel magnetic powder core coating granulation powder with soft collapse defects from a certain batch. The angle of repose was tested to be 51°. It was then subjected to secondary treatment according to the process parameters of Example 1: 7.5 kg (15%) of acetone was added and stirred to dissolve. 200 g (0.4%) of epoxy resin was added to supplement the binder. The mixture was then granulated through a 40-mesh sieve and dried at 100°C for 3 hours.
[0096] Approximately 49.2 kg of recycled powder was obtained after processing, with a recovery rate of approximately 98.4%. The recycled powder had a distinct granular texture, was dry, had an angle of repose of 33°, and a moisture content of 0.65%, which met the control requirements of 0.6% to 0.7%.
[0097] Recycled powder and normal powder were mixed at mass ratios of 1:3 and 1:1, respectively, and then used for pressing and molding. The magnetic performance test results of the resulting magnetic core products are as follows: (1) Mixed at a ratio of 1:3 (recycled powder accounts for 25%): effective magnetic permeability is 62.2 (normal powder is 63.1, deviation is 1.4%), and core loss is 283 mW / cm. 3 (Normal powder is 278 mW / cm) 3 (with a deviation of 1.8%), the product qualification rate reached over 99%.
[0098] (2) Mixed in a 1:1 ratio (50% recycled powder): effective magnetic permeability is 62.0 (63.1 for normal powder, deviation 1.7%), core loss is 282 mW / cm 3 (Normal powder is 278 mW / cm) 3 (with a deviation of 1.4%), the product qualification rate reached over 98.5%.
[0099] The above results indicate that, regardless of whether the recycled powder is mixed with the normal powder in a ratio of 1:3 or 1:1, the magnetic properties of the resulting magnetic core products are not significantly different from those of products using only the normal powder, and are all within the allowable deviation range in engineering.
[0100] This disclosed method is applicable to the coating and granulation process of various metal magnetic powder cores. In actual production, when powder softening defects occur, the defective powder can be collected and subjected to secondary processing at any time. The processed powder can be mixed with normal powder in a certain proportion or used alone. This method does not require additional special equipment and can be implemented using existing granulation and drying equipment, thus possessing good industrial application value.
[0101] The above description is merely a preferred embodiment of this disclosure and is not intended to limit this disclosure. Various modifications and variations can be made to this disclosure by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the scope of protection of this disclosure.
Claims
1. A secondary treatment method for defective powder materials coated with metal magnetic powder cores, characterized in that, Includes the following steps: (1) Take the defective metal magnetic powder core material that has been coated with binder, dried and granulated and is in a soft state; The term "soft and limp state" refers to a state where the graininess is not obvious and the fluidity is poor. (2) Add organic solvent to the defective powder described in step (1), stir evenly, so that the solidified binder in the powder can be redissolved and the powder can be restored to a wet state; The moist state refers to a paste-like or plastic state; (3) Add supplementary binder to the wet material obtained in step (2), stir evenly, so that the supplementary binder is mixed with the original binder; The amount of the supplementary binder added is 0.1% to 1.0% of the mass of the defective powder; (4) The material obtained in step (3) is granulated and dried to obtain recycled powder.
2. The secondary processing method according to claim 1, characterized in that, In step (1), the angle of repose of the defective powder is 45° or higher.
3. The secondary processing method according to claim 1, characterized in that, In step (2), the amount of organic solvent added is 5% to 30% of the mass of the defective powder.
4. The secondary processing method according to claim 1, characterized in that, In step (2), the organic solvent is selected from one or more of acetone, ethanol, toluene, and xylene.
5. The secondary processing method according to claim 1, characterized in that, In step (3), the supplementary binder is the same type of binder used in the initial coating granulation in step (1).
6. The secondary processing method according to claim 1, characterized in that, In step (3), the supplementary adhesive is selected from one or more of epoxy resin, silicone resin, and phenolic resin.
7. The secondary processing method according to claim 1, characterized in that, In step (3), the amount of supplementary binder added is 0.2% to 0.6% of the mass of the defective powder.
8. The secondary processing method according to claim 1, characterized in that, In step (4), the granulation is carried out by sieve granulation or high-speed stirring granulation, and the granulation mesh is 20 mesh to 120 mesh.
9. The secondary processing method according to claim 1, characterized in that, In step (4), the drying temperature is 60℃~150℃ and the drying time is 1~6 hours.
10. The secondary processing method according to claim 1, characterized in that, In step (4), the moisture content of the obtained recycled powder is 0.6%~0.7%.
Citation Information
Patent Citations
Metal magnetic powder core with low magnetic conductivity and low loss as well as preparation method and application of metal magnetic powder core
CN118658692A